THE PARTICE OF THE ISRA’ MI’RAJ VALUE OF THE MANDAILING NATAL COMMUNITY - Putra, Dedisyah; Hamid, Asrul (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
Isra' Mi'raj is a very important historical event for Muslims around the world. In Islam, the commemoration of Isra' and Mi'raj is a momentum to upgrade faith, add insight and motivation to worship, especially in maintaining the five daily prayers. The journey of Isra' Mi'raj is believed to be the most sacred prophetic spiritual journey, so it is natural that many Quraysh residents of Mecca at that time doubted its truth. Commemorating Isra' and Mi'raj including the realm of ikhtilaf al-fuqaha from the past until now. But the most mu'tabar opinion states the ability (al-Jawaz) in commemorating Isra' Mi'raj to achieve benefit for the religious community. This opinion is believed by the Muslim community in Mandailing Natal Regency. This paper presents a portrait of the habits of Muslims in Mandailing Natal Regency in commemorating Isra' and Mi'raj as one of the efforts to foster religious spirit to make Mandailing Natal Regency a civilized one. This research is a field research with a qualitative method with a religious approach to explain the practice of religious spirit that should bring every Muslim in Mandailing Natal Regency to practice Islamic teachings in accordance with the spirit contained in the Isra' and Mi'raj events. In addition, the custom of the Mandailing Natal community in commemorating Isra' and Mi'raj needs to be maintained and preserved as a form of local wisdom in order to realize Mandailing Natal which has the slogan of a traditional country, obedient to worship.Isra’ Mi’raj adalah peristiwa bersejarah yang sangat penting bagi umat Islam seluruh dunia. Dalam Islam, peringatan Isra’ dan Mi’raj merupakan momentum untuk mengupgrade keimanan, menambah wawasan dan motivasi beribadah terutama dalam menjaga salat lima waktu. Perjalanan Isra’ Mi’raj diyakini sebagai perjalanan rohani kenabian yang paling sakral sehingga wajar bila penduduk kafir Quraisy Kota Makkah saat itu banyak yang meragukan akan kebenarannya. Memperingati Isra’ dan Mi’raj termasuk ranah ikhtilaf al-fuqaha dari dahulu sampai sekarang. Namun pendapat yang paling mu’tabar menyatakan kebolehan (al-jawaz) dalam memperingati Isra’ Mi’raj untuk mencapai maslahat bagi masyarakat beragama. Pendapat inilah yang diyakini oleh masyarakat muslim di Kabupaten Mandailing Natal. Tulisan ini menyajikan potret kebiasaan umat Islam di Kabupaten Mandailing Natal dalam memperingati Isra’ dan Mi’raj sebagai salah satu upaya memupuk semangat beragama menjadikan Kabupaten Mandailing Natal yang madani. Penelitian ini merupakan field research dengan metode kualitiatif dengan pendekatan keagamaan guna menjelaskan praktik semangat keagamaan yang seharusnya membawa setiap umat Islam di Kabupaten Mandailing Natal mengamalkan ajaran Islam sesuai dengan spirit yang terkandung pada peristiwa Isra’ dan Mi’raj. Selain itu, kebiasaan masyarakat Mandailing Natal dalam memperingati Isra’ dan Mi’raj ini perlu dijaga dan dilestarikan sebagai bentuk kearifan lokal guna mewujudkan Mandailing Natal yang memiliki slogan negeri beradat, taat berbibadat.